FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN SEBELUM DAN DI MASA COVID-19 - Melania Amelita; Yanti Yanti (Jurnal Paradigma Akuntansi, 2026)
This research aims to find out how the influence of variables that affect company value before and during the Covid-19 pandemic on basic materials companies listed on the IDX during 2018-2021. Sample was chosen by purposive sampling method and the valid data was 30 companies. Data processing methods with multiple regression analysis helped by SPSS program and Microsoft Excel 2019. The test results before the pandemic showed that company size had an effect on firm value, while capital structure, profitability and audit quality had no effect on firm value. Test results during the pandemic showed that capital structure, profitability, and company size had an effect on firm value, while audit quality had no effect on firm value. The results of the different test gave conclusion that there is no distinction in the average firm value before and during the covid-19 pandemic period. The implication of this research is the need for adaption to conditions with uncertain circumstances and carry out financial management strategies so that decisions taken provide added value to the company.